Does sports-specific training improve measures of impairment developed for para sport classification? A multiple-baseline, single-case experiment - Wilson, P. J.; Connick, M. J.; Dutia, I. M.; Beckman, E. M.; Macaro, A.; Tweedy, S. M. (Journal of Sports Sciences, 2021)
Conceptually, sports-specific training should not influence measures of impairment used to classify Para athletes. This study evaluated the extent to which measures of strength, range of movement and coordination developed for Para swimming classification changed in response to a performance-focused swimming programme. A five-phase multiple-baseline, single-case experimental research design was utilized. Three participants with cerebral palsy and high support needs completed the 64-week study, which included two 16-week performance-focused swimming training blocks. Swimming speed, isometric shoulder extension strength, shoulder flexion range of movement and upper limb coordination were monitored throughout.